2002
DOI: 10.1002/ar.10123
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin‐1 expression in the chick embryo chorioallantoic membrane

Abstract: The chick embryo chorioallantoic membrane (CAM) is commonly used in vivo to study both angiogenesis and anti-angiogenesis. Rapid membrane water transport is mediated by a family of molecular water channels, called aquaporins (AQPs), which have been identified in the epithelial and endothelial cells of higher vertebrates. AQP1, expressed in adsorptive and secretory epithelia, is also expressed in endothelial cells of capillaries and arteries. Its mRNA has been found in vascular smooth muscle cells (VSMCs) of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The mRNA levels of rat AQPs 1, 3, and 4 reached maximum at the time of birth, whereas the level of rat AQP2 mRNA continued to increase postnatally for 10 days [6] and 4 weeks [76]. AQP1 homologue is also expressed at ectodermal and endodermal epithelia and chorioallantoic membrane blood vessels (endothelium and smooth muscle) of chick embryos [65].…”
Section: Aqps During Development and Maturationmentioning
confidence: 95%
“…The mRNA levels of rat AQPs 1, 3, and 4 reached maximum at the time of birth, whereas the level of rat AQP2 mRNA continued to increase postnatally for 10 days [6] and 4 weeks [76]. AQP1 homologue is also expressed at ectodermal and endodermal epithelia and chorioallantoic membrane blood vessels (endothelium and smooth muscle) of chick embryos [65].…”
Section: Aqps During Development and Maturationmentioning
confidence: 95%
“…The trophoectoderm gives rise to the placenta and chorion; aquaporins 1, 3, 8 and 9 are water channel genes previously reported to be in the placenta and/or chorion of the human and sheep [18-21]. AQP1 has also been reported to be in the chick chorioallantoic membrane [22]. AQP1 is in the vasculature and AQP3 and 9 are in the apical membranes of human and ovine term placenta and chorion.…”
Section: Placenta and Fetal Fluid Compartmentsmentioning
confidence: 99%
“…Davis et al (1988) suggested by using water-stressed developing eggs that the action of the CAM was an integral component of the osmoregulatory system of the chick embryo. A family of molecular water channels, aquaporins, was expressed in CAM blood vessels and increased from embryonic day 10 (Ribatti et al, 2002).…”
Section: Discussionmentioning
confidence: 99%